Multimodal Visual Social Semiotic Analysis of Political Campaigns Media: A Case Study of the Amin Banner in the 2024 Indonesian Presidential Election - Annisaa Syifa Nuramalina; Eva Leiliyanti; Miftahulkhairah Anwar (Green Publisher Indonesia, 2026)
In the 2024 Indonesian presidential election, campaign props such as banners and billboards function not only as promotional media but also as sites of ideological representation and symbolic political communication. This study aims to examine how visual elements in campaign banners construct the political identity of the Anies Baswedan–Muhaimin Iskandar (AMIN) candidate pair through the lens of visual social semiotics. Employing a qualitative case study approach, the research applies Kress and van Leeuwen’s multimodal discourse framework to analyze the representational, interpersonal, and compositional metafunctions embedded in selected AMIN campaign banners. Data were collected through field observation and visual documentation and then purposively selected based on analytical relevance. The findings reveal that the AMIN campaign strategically organizes visual structures—such as gaze, gesture, color, spatial composition, and symbolic attributes—to project an image of inclusivity, credibility, and ideological commitment to social change. By integrating social semiotic theory with empirical analysis of Indonesian political campaign media, this study contributes to a deeper understanding of how multimodal visual resources function as persuasive and meaning-making tools in contemporary electoral politics.